2009
DOI: 10.1007/s11205-009-9563-1
|View full text |Cite
|
Sign up to set email alerts
|

Reconciliation Sentiment Among Victims of Genocide in Rwanda: Conceptualizations, and Relationships with Mental Health

Abstract: Reconciliation sentiment, Mental health, Rwanda,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
4
19
0
6
Order By: Relevance
“…Overall, the present findings were consistent with the previous ones (López López et al, 2013 and similar to those of Nadler and Liviatan (2006) among Jewish students living in Israel and of Staub, Pearlman, Gubin, & Hagengimana (2005), Mukashema and Mullet (2010), Heim and Schaal (2014) in Rwanda, and Arnoso Martinez, Cardenas Castro, and Páez Rovira, (2015) in Chile. In all cases, the damage caused was severe, but the political situation had objectively improved as a result of the demobilization and of the peace process).…”
Section: Always Forgivesupporting
confidence: 93%
“…Overall, the present findings were consistent with the previous ones (López López et al, 2013 and similar to those of Nadler and Liviatan (2006) among Jewish students living in Israel and of Staub, Pearlman, Gubin, & Hagengimana (2005), Mukashema and Mullet (2010), Heim and Schaal (2014) in Rwanda, and Arnoso Martinez, Cardenas Castro, and Páez Rovira, (2015) in Chile. In all cases, the damage caused was severe, but the political situation had objectively improved as a result of the demobilization and of the peace process).…”
Section: Always Forgivesupporting
confidence: 93%
“…A negative, although weak, association was found between intergroup forgiveness and mental health. Mukashema and Mullet (2010) examined the relationship between reconciliation sentiment and mental health among 194 primary victims of the genocide of the Tutsis in Rwanda. A positive association was found between interpersonal reconciliation sentiment (i.e., the renewed capacity to interact again on a daily basis with former opponents) and mental health.…”
Section: Dispositional Forgiveness and Ptsdmentioning
confidence: 99%
“…Research in South Sudan prior to the recent conflict found probable PTSD rates of 36–48% [35], and women with more trauma exposure had less optimistic views of the probability of peace [6]. Studies in Rwanda, Uganda, the Democratic Republic of Congo, Kosovo, and Cambodia have found that people with PTSD have less positive attitudes toward trials for people suspected of atrocities [7], less positive beliefs in a communal or interdependent vision of the future [7, 8], more feelings of revenge and hatred and less willingness to forgive or reconcile [914], less satisfaction with punishment of perpetrators, apologies by perpetrators, and remuneration for suffering [13], and are more likely to endorse violent means of ending conflict [15]. In contrast, one study in Afghanistan did not find a relationship between PTSD symptoms and feelings of hatred [16].…”
Section: Introductionmentioning
confidence: 99%